Experience the power of community-driven knowledge on IDNLearn.com. Discover detailed and accurate answers to your questions from our knowledgeable and dedicated community members.
Sagot :
To express [tex]\(\frac{f(x+h) - f(x)}{h}\)[/tex] in its simplest form for the function [tex]\(f(x) = 2x^2 - x + 1\)[/tex], we can follow these steps:
1. Determine [tex]\(f(x+h)\)[/tex]:
Given [tex]\(f(x) = 2x^2 - x + 1\)[/tex], we need to find [tex]\(f(x+h)\)[/tex].
[tex]\[ f(x+h) = 2(x+h)^2 - (x+h) + 1. \][/tex]
2. Expand [tex]\(f(x+h)\)[/tex]:
[tex]\[ f(x+h) = 2(x^2 + 2xh + h^2) - x - h + 1. \][/tex]
[tex]\[ f(x+h) = 2x^2 + 4xh + 2h^2 - x - h + 1. \][/tex]
3. Compute [tex]\(f(x+h) - f(x)\)[/tex]:
Subtract [tex]\(f(x)\)[/tex] from [tex]\(f(x+h)\)[/tex]:
[tex]\[ f(x+h) - f(x) = (2x^2 + 4xh + 2h^2 - x - h + 1) - (2x^2 - x + 1). \][/tex]
Simplify the expression:
[tex]\[ f(x+h) - f(x) = 4xh + 2h^2 - h. \][/tex]
4. Form [tex]\(\frac{f(x+h) - f(x)}{h}\)[/tex]:
[tex]\[ \frac{f(x+h) - f(x)}{h} = \frac{4xh + 2h^2 - h}{h}. \][/tex]
5. Simplify by dividing each term by [tex]\(h\)[/tex]:
[tex]\[ \frac{4xh + 2h^2 - h}{h} = \frac{4xh}{h} + \frac{2h^2}{h} - \frac{h}{h}. \][/tex]
[tex]\[ \frac{4xh}{h} + \frac{2h^2}{h} - \frac{h}{h} = 4x + 2h - 1. \][/tex]
Hence, the simplified form of [tex]\(\frac{f(x+h) - f(x)}{h}\)[/tex] is:
[tex]\[ \boxed{2h + 4x - 1}. \][/tex]
1. Determine [tex]\(f(x+h)\)[/tex]:
Given [tex]\(f(x) = 2x^2 - x + 1\)[/tex], we need to find [tex]\(f(x+h)\)[/tex].
[tex]\[ f(x+h) = 2(x+h)^2 - (x+h) + 1. \][/tex]
2. Expand [tex]\(f(x+h)\)[/tex]:
[tex]\[ f(x+h) = 2(x^2 + 2xh + h^2) - x - h + 1. \][/tex]
[tex]\[ f(x+h) = 2x^2 + 4xh + 2h^2 - x - h + 1. \][/tex]
3. Compute [tex]\(f(x+h) - f(x)\)[/tex]:
Subtract [tex]\(f(x)\)[/tex] from [tex]\(f(x+h)\)[/tex]:
[tex]\[ f(x+h) - f(x) = (2x^2 + 4xh + 2h^2 - x - h + 1) - (2x^2 - x + 1). \][/tex]
Simplify the expression:
[tex]\[ f(x+h) - f(x) = 4xh + 2h^2 - h. \][/tex]
4. Form [tex]\(\frac{f(x+h) - f(x)}{h}\)[/tex]:
[tex]\[ \frac{f(x+h) - f(x)}{h} = \frac{4xh + 2h^2 - h}{h}. \][/tex]
5. Simplify by dividing each term by [tex]\(h\)[/tex]:
[tex]\[ \frac{4xh + 2h^2 - h}{h} = \frac{4xh}{h} + \frac{2h^2}{h} - \frac{h}{h}. \][/tex]
[tex]\[ \frac{4xh}{h} + \frac{2h^2}{h} - \frac{h}{h} = 4x + 2h - 1. \][/tex]
Hence, the simplified form of [tex]\(\frac{f(x+h) - f(x)}{h}\)[/tex] is:
[tex]\[ \boxed{2h + 4x - 1}. \][/tex]
We appreciate your participation in this forum. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Your questions find answers at IDNLearn.com. Thanks for visiting, and come back for more accurate and reliable solutions.